Cloning of lactoferrin gene of mice and the difference of lactoferrin gene expression in mammary gland at different lactation stages - WANG Yi-zhen; HAN Fei-fei; HUANG Hai-qing (浙江大学学报. 农业与生命科学版)
Total RNA was extracted from mammary gland of mice. Two primers were designed and synthesized according to the murine lactoferrin gene reported in Genbank. A cDNA fragment about 897 bp in length was obtained through RT-PCR. The PCR product was cloned into pGEM-T vector and then sequenced. Sequence analysis suggested that this fragment corresponded to a portion of the sequence of lactoferrin cDNA and coded 299 amino acid residues, which constituted the major part of mature lactoferrin. The gene homology of fragment obtained in this study was 99% comparable to that of the reported lactoferrin cDNA sequence in uterus of mice. Based on the lactoferrin gene clone, we successfully constructed an optimal semi-quantitative RT-PCR method. Using β-actin as inner control, we detected the difference in expression of lactoferrin gene at different lactation stages of mice. The results showed that the amount of lactoferrin gene expression changed with lactation stages, it decreased from day 1 of lactation to day 18 of lactation, but during involution of mice mammary gland (day 25 of lactation), lactoferrin gene expression increased.